Service Recovery Performance: The Effect Of Management Commitment To Service Quality Among The Frontline Hotel Employees Through Work Engagement And Job Embeddedness - Hamir, Norhamizan (2020)
Service recovery performance is crucial in the hotel industry as it reflects the action or behaviour of the frontline employees when encountering a service failure. The success of handling a service recovery situation may rely upon the commitment of the management towards upholding service quality. In this study, the management commitment to service quality which is manifested through service training, empowerment, reward, teamwork and customer complaint management, is examined in relation to service recovery performance. Work engagement and job embeddedness have mediating roles in the evaluation of service performance in this study. The Social Exchange Theory and Reformulation of Attitude Theory were employed as the grounded theory to assess the relationship. The data were obtained from self-administered questionnaires which focused on the frontline employees of four and five-stars hotels in Malaysia. A total of 313 participants were involved and they represented 35.98% of the response rate. A Partial Least Squares (PLS-SEM) approach was used to analyze the hypotheses developed to establish the direct and indirect positive significant relationship between management commitment to service quality as well as the role of work engagement and job embeddedness as the intervening variables in the service recovery performance.